Synthesis of bilayer ZnO nanowire arrays: Morphology evolution, optical properties and photocatalytic performance. Issue 9 (November 2015) - Liu, Xinmei; Huang, Wenyi; Huang, Guoxia; Fu, Fengming; Cheng, Hao; Guo, Weimin; Li, Junsheng; Wu, Hongda
Abstract: A novel hierarchical zinc oxide three-dimensional architecture of densely packed and well-aligned bilayer ZnO nanowire arrays was synthesized via a hydrothermal process. For ZnO nanowire growth, a layer of dense zinc microplatelet arrays was first obtained on copper foil by an electroplating method. Uniform ZnO nanowires were grown vertically on both surfaces of zinc microplatelet in hydrothermal solution only containing ammonia water. The obtained ZnO nanowire arrays possessed high packing density and uniform size, demonstrating a rapid nucleation and growth process in the initial stage of growth. But then Ostwald ripening dominated the morphology evolution of hierarchical ZnO architecture due to a low degree of supersaturation of ZnO. XRD and HRTEM characterizations confirmed ZnO possessing a highly crystalline nature with preferential (002) orientations along the c -axis direction. With the decrease of ZnO nanowire size, the absorption spectra of hierarchical ZnO film exhibited an increase of visible light absorption and slight red-shift of band gap, whereas its emission spectra exhibited a decrease of photoluminescence intensity, which can be ascribed to the increase of defects in ZnO structure with size decrease. The photocatalytic experiment indicated that the hierarchical nanostructure film had superior photocatalytic performance in the degradation of methyl orange solution under ultraviolet irradiation. The work also presented a simple approach for further practical application of ZnO nanowire arrays to nanoscale optoelectronic device.